Beginning NetBeans IDE : for Java developers - Wielenga, Geertjan (Expert's voice in Java., 2015)
This is a guide for getting started learning and using the free and open source NetBeans IDE. It shows you what the IDE is all about and how to use it with real-world case studies built from the ground up as you learn all about the IDE. You'll learn what NetBeans is and how to use it; how to install and set up your NetBeans IDE and environment; how to write your first Java application using NetBeans; how to explore the key NetBeans wizards and plug-ins; how to build a complex Java EE-based application using Maven with NetBeans; how to improve applications by refactoring, testing, debugging, and profiling. --